The Deleterious Effects of Impaired Fibrinolysis on Skeletal Development Are Dependent on Fibrin(ogen), but Independent of Interlukin-6 - Cole, Heather A.; Moore-Lotridge, Stephanie N.; Hawley, Gregory D.; Jacobson, Richard; Yuasa, Masato; Gewin, Leslie; Nyman, Jeffry S.; Flick, Matthew J.; Schoenecker, Jonathan G. (Frontiers in Cardiovascular Medicine, 2021)
Chronic diseases in growing children, such as autoimmune disorders, obesity, and cancer, are hallmarked by musculoskeletal growth disturbances and osteoporosis. Many of the skeletal changes in these children are thought to be secondary to chronic inflammation. Recent studies have likewise suggested that changes in coagulation and fibrinolysis may contribute to musculoskeletal growth disturbances. In prior work, we demonstrated that mice deficient in plasminogen, the principal protease of degrading and clearing fibrin matrices, suffer from inflammation-driven systemic osteoporosis and that elimination of fibrinogen resulted in normalization of IL-6 levels and complete rescue of the skeletal phenotype. Given the intimate link between coagulation, fibrinolysis, and inflammation, here we determined if persistent fibrin deposition, elevated IL-6, or both contribute to early skeletal aging and physeal disruption in chronic inflammatory conditions. Skeletal growth as well as bone quality, physeal development, and vascularity were analyzed in C57BL6/J mice with plasminogen deficiency with and without deficiencies of either fibrinogen or IL-6. Elimination of fibrinogen, but not IL-6, rescued the skeletal phenotype and growth disturbances in this model of chronic disease. Furthermore, the skeletal phenotypes directly correlated with both systemic and local vascular changes in the skeletal environment. In conclusion, these results suggest that fibrinolysis through plasmin is essential for skeletal growth and maintenance, and is multifactorial by limiting inflammation and preserving vasculature.